Structured Digital Writing Lab: Workflow, Application and Evaluation - Uckelmann, Dieter; Judel, Sven; Görzen, Sergej; Greven, Christoph; Schroeder, Ulrik (International Journal of Online and Biomedical Engineering (iJOE), 2022)
The importance of writing and publishing is well understood in the academic world and is gaining importance in business applications as well. Students need to gain corresponding skills during their studies. The process itself can be structured and is repeatable. However, students are not familiar with the process and need some guidance to achieve high quality results. Typical writing seminars may be quite theoretical and do not sufficiently guide the writing in teams, reviewing and publication process. This paper presents the Scientific Workflow Guide SWOFI that can be used to guide collaborative academic writing and publishing in a structured process, which resembles the guided process in lab-based education. The results which have been achieved in different seminars at two different institutions are analyzed and discussed.